Progetto PEDROS - Perimetrazione automatica di incEndi con DRone equipaggiato con sensOre Specifico - SISTEMI, ALMA (GEOmedia, 2023)
The proposed system provides for the development of a SAPR system (Airborne Remote Pilotage System) which can be of assistance to the detailed perimeter, of wooded areas attacked by insects/pathogens and/or by forest fires in order to transmit to the competent authorities the certification of these areas affected by environmental damage, in compliance with current legislation. This activity is normally carried out through the interpretation of satellite image analyzes with spatial resolutions that are not always adequate for the purpose, which often entails the need for re-perimeteration in the field carried out by operators equipped with GNSS handheld systems.